Hubungan Power Otot Tungkai Dengan Kemampuan Tendangan Melambung Jauh Pemain Sepak Bola Siswa SMP Negeri 15 Kabupaten Seram Bagian Timur. - Iwan Rimodar; B. Hasbullah; J. Matitaputty (Peneliti.net, 2026)
This study aimed to determine the relationship between leg muscle power and long lob kick ability among soccer players at SMP Negeri 15 East Seram Regency. The study was motivated by the relatively low ability of many students to perform long lob kicks, which was presumed to be influenced by physical condition, particularly leg muscle power. This research employed a quantitative method with a correlational research design. The population consisted of all 58 students participating in the school's soccer extracurricular program at SMP Negeri 15 East Seram Regency. The sample comprised 30 students selected using the simple random sampling technique. The instruments used were the Standing Broad Jump Test to measure leg muscle power and the Long Lob Kick Test to assess long lob kick ability. Data were analyzed using the Pearson Product-Moment Correlation. The results showed that the correlation coefficient was r = 0.847, while the critical value of r at the 5% significance level with 28 degrees of freedom (df) was 0.361. Since the calculated correlation coefficient (0.847) was greater than the critical value (0.361), the alternative hypothesis (Ha) was accepted and the null hypothesis (H₀) was rejected. These findings indicate a positive and significant relationship between leg muscle power and long lob kick ability. The greater the players' leg muscle power, the better their ability to perform long lob kicks.